ChemInform Abstract: Platinum(II) Schiff Base Complexes as Photocatalysts for Visible‐Light‐Induced Cross‐Dehydrogenative Coupling Reactions. Issue 8 (February 2016) - Shelar, Deepak Prakash; Li, Ting‐Ting; Chen, Yong; Fu, Wen‐Fu
Abstract: Four platinum(II) schiff base complexes are synthesized and one of them is examined in the visible‐light‐induced coupling reactions of tetrahydroisoquinolines (I) with different nucleophiles.